Consumer Perceptions Towards Global Brands, A Malaysian Perspective - Lim, Jenny Marisa Dao Siang (2008)
The purpose of this study is to elucidate and focus specifically n Malaysia on how Malaysian consumer's perception are towards global brands. Based on the previous study a simple conceptual framework has been developed and for hypotheses were put into test. The theoretical framework is used to explain the relationship between the four global brand dimensions and the consumers' perceptions, which influence their buying behaviour.